Этапы становления политической элиты в Украине в годы независимости - Шульга, Н. (Социология: теория, методы, маркетинг, 2006)
The purpose of this paper is to review the process of formation of the Ukrainian ruling elite and to determine the main stages. The attention is focused mainly on the political elite. Besides, there are mentioned such categories, as military and force elite, administrative and power, scientific elite, business elite, as well as criminal one. The author makes up a conclusion that the elites may be consolidated on the basis of common projects, which are aimed at the solution of actual problems and looking for new ways to meet challenges of the future.